2019
DOI: 10.5902/2179460x32305
|View full text |Cite
|
Sign up to set email alerts
|

The life of dragonflies: order Odonata

Abstract: The Odonata Order has a wide geographical distribution. The life cycle is complex, with stage of aquatic nymph, the naiad and winged adults. The research was carried out in peer-reviewed journals at the PuMed and Capes databases, with the keyword Odonata "and" ecology, when the text was complete and available. The used books were researched with insects theme, entomology, available in the collection of the library of the Federal University of the Triângulo Mineiro or private collection. The theoretical framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…1,2 The increased taxonomic information that we have nowadays led to more studies about Odonata in Brazil considering how easy is to be observed and captured by the fascination created by this group. [3][4][5] Most of these surveys are about description of new species and their respective ecologic role 6 and geographic distribution. [7][8][9][10] There is a lack of information in many Brazilian regions due to the absence of infrastructure, logistic and study group.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The increased taxonomic information that we have nowadays led to more studies about Odonata in Brazil considering how easy is to be observed and captured by the fascination created by this group. [3][4][5] Most of these surveys are about description of new species and their respective ecologic role 6 and geographic distribution. [7][8][9][10] There is a lack of information in many Brazilian regions due to the absence of infrastructure, logistic and study group.…”
Section: Introductionmentioning
confidence: 99%